Penerapan Algoritma Fisher Yates Shuffle Pada Aplikasi Quiz Game Pengenalan Budaya Betawi Berbasis Android (Studi Kasus: Tempat Kursus Rumah Aljabar) - Daniel Prastyo; Hadi Zakaria (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The Betawi tribe is an indigenous tribe from the city of Jakarta. The Betawi people have lived in the Jakarta City area since the Dutch colonial era. The spread of the Betawi tribe which was quite still at that time in several areas made it have many habits and customs. Along with the development of the times, the lack of interesting media and tools that keep up with technological advances to provide deeper knowledge about Betawi Culture to children, has an impact on children's lack of interest in learning Betawi Culture. The purpose of developing this application is to design an interesting android-based learning game by applying the Fisher Yates Shuffle Algorithm to randomize the types of questions. To make this learning game quiz application use MySql as a database storage for the types of questions. And this application also utilizes the MDLC (Multimedia Development Life Cycle) model which consists of 6 stages, namely concept, design, material collecting, assembly, testing and distribution. It is hoped that this game quiz can increase children's interest in learning Betawi Culture because the learning media is interesting. As well as the Fisher Yates Shuffle Algorithm that is applied can test the child's dexterity in remembering each question to be randomized.